2020
DOI: 10.1089/end.2019.0873
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Evaluation of Urinary Stone Comminution with a Clinical Burst Wave Lithotripsy System

Abstract: Objective: Our goals were to validate stone comminution with an investigational burst wave lithotripsy (BWL) system in patient-relevant conditions and to evaluate the use of ultrasonic propulsion to move a stone or fragments to aid in observing the treatment endpoint. Materials and Methods: The Propulse-1 system, used in clinical trials of ultrasonic propulsion and upgraded for BWL trials, was used to fragment 46 human stones (5-7 mm) in either a 15-mm or 4-mm diameter calix phantom in water at either 50% or 7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 30 publications
2
15
0
1
Order By: Relevance
“…Compared with extracorpo-real shockwave lithotripsy (SWL), BWL may provide an officebased modality for stone management solely driven by ultrasonic (US) technologies to image, fragment, and reposition stones in the kidney. In this in vitro study, 3 the authors confirm that 5-7 mm kidney stones of various compositions can be comminuted within 30 minutes in tissue phantoms under clinically relevant test environments. Moreover, the potential of US…”
supporting
confidence: 63%
“…Compared with extracorpo-real shockwave lithotripsy (SWL), BWL may provide an officebased modality for stone management solely driven by ultrasonic (US) technologies to image, fragment, and reposition stones in the kidney. In this in vitro study, 3 the authors confirm that 5-7 mm kidney stones of various compositions can be comminuted within 30 minutes in tissue phantoms under clinically relevant test environments. Moreover, the potential of US…”
supporting
confidence: 63%
“…The system has previously been used to effectively comminute stones 3e7 mm in size ex vivo. 17 Table 1 shows the BWL exposure parameters. BWL was delivered at a frequency of 390 kHz to break stones consistently into 2 mm fragments.…”
Section: Investigational Device and Exposure Parametersmentioning
confidence: 99%
“…This was used in the first clinical trial discussed below [20]. Following that trial, the device was refined to provide broader beams and longer duration exposures for ultrasonic propulsion and enabled BWL pulses with the same transducer [21][22][23][24]. The iteration of the hand held transducer used in most propulsion and BWL clinical trials to date uses a 350 kHz and 60 mm single element annular element for therapy (H209, Sonic Concepts, Bothell WA) and has within the aperture a phased array transducer (P4-2, Philips/ATL, Bothell, WA) for image guidance.…”
Section: Bme Frontiersmentioning
confidence: 99%
“…The authors concluded that real-time US may help to facilitate monitoring of BWL and prevent renal injury. Ramesh et al tested BWL on 46 human stones within a phantom model of the human kidney, finding that 89% of stones were comminuted within 30 minutes and 70% within 10 minutes of treatment [ 23 ]. Incorporating ultrasonic propulsion during a BWL treatment session is thought to provide benefit in determining the endpoint of fragmentation when small stone fragments are cleared from the treatment area.…”
Section: Burst Wave Lithotripsymentioning
confidence: 99%